The remarkable pioneering contribution of Gaspar Vianna to the study of the neuropathology of Chagas disease - Pittella, José Eymard Homem (Arquivos de Neuro-Psiquiatria, 2018)
Gaspar Vianna is considered one of the great names in Medicine and Science in Brazil. Yet, little prominence has been given to his studies in Neuropathology. He was the first to describe, in 1911, the histopathology and pathogenesis of chagasic encephalitis in the acute phase of Chagas disease, as well as the intracellular life cycle of Trypanosoma cruzi. Over 100 years have elapsed and Gaspar Vianna's pioneering study remains an example of a meticulous and still up-to-date description of central nervous system involvement in the acute phase of Chagas disease.
Keywords: Chagas disease; neuropathology; history